The Form Of Resolving The Laka Lalu Case With A Restorative Justice Approach According To Police Regulation Number 8 Of 2021 On Handling Criminal Acts Based On Restorative Justice - Ardyan Ardyan; Ariman Sitompul; Ruslan Ruslan (Universitas Dharmawangsa, 2023)
AbstractJudicial procedures in Indonesia in resolving criminal cases have not been in accordance with the wishes society to feel fair in law. People who feel less Justice issued opinion or criticism of judicial procedures in indonesia. The problem of traffic accidents refers to the act No. 22/2009 on LLAJ and Criminal Procedure Code. The second legal basis for the settlement of traffic accident cases it is not yet possible to solve problems based on restorative justice. This research aims to find out and analyze procedures to solve the problems of past accidents traffic that can cause casualties both serious injuries and fatalities using the approach of Justice restorative justice according to police Regulation Number 8 of 2021 on handling criminal acts based on Justice Restorative, a form of settlement of accident cases and then with a restorative justice approach according to the police Perarturan Number 8 of 2021 on handling criminal acts based on restorative justice and legal certainty to resolve the issue of laka and then with a restorative justice approach. Methods used in this research using empirical approach and normative juridical approach to the paradigm of analysis qualitative data. Research and Discussion: 1. Legal arrangement for settlement of traffic accident cases it is not based on restorative justice. 2. Legal weaknesses in the settlement of traffic accident cases using a restorative justice approach. 3. Reconstruction of last accident settlement law cross with restorative justice approach,Â namely by revising the provisions of Article 230 and Article 235 U.S. No. 22/2009 on LLAJ, so that the case of traffic accidents light, medium and heavy can based on restorative justice. Excluded against traffic accidents that cause casualties soul, the resolution of things based on restorative justice does not drop the prosecution of thingsKeywords: Settlement Of Traffic Matters, Justice, Restorative.